EXAFS characterization of PtNi bimetallic catalyst applied to glycerol liquid-phase conversion - Barbelli, Maria Laura (2014)
The aim of this work is to evaluate the catalytic properties (activity, selectivity, and stability) of PtNi catalysts supported on Ce−Zr−α-Al2O3 (CZA) in the liquid-phase conversion of glycerol and to relate them to the results of the EXAFS characterization. The PtNi/CZA catalyst presents the highest global activity and promotes the formation of liquid oxygenated hydrocarbons, mainly acetol and 1,2-propylene glycol, which are formed from glycerol hydrogenolysis. By means of EXAFS studies, it was determined that three phases are present: a PtNi3 nanoalloy, unalloyed metallic Pt with high dispersion, and unalloyed metallic Ni. The highest activity of the PtNi/CZA could be assigned to the presence of the PtNi3 alloy, which results in a more active phase than the Pt and Ni sites separately. The PtNi/CZA is the more stable, and the EXAFS results show that this behavior would be associated with the presence of the PtNi3 alloy nanoparticles on the surface of the Ni particles with low mobility.